Pengaruh Mekanisme Bonus, Tunneling Incentive, dan Debt Covenant Terhadap Transaksi Transfer Pricing - Istiqomah; Baihaqi Fanani (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
The Effect of Bonus Mechanisms, Tunneling Incentive and Debt Covenant on Transfer Pricing Transactions. (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2018).This study aims to determine the effect of bonus mechanism, tunneling incentive and debt covenants on transfer pricing transactions in manufacturing companies listed on the Indonesia Stock Exchange in the period of 2014-2018.The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2018. By using purposive sampling method which consists of 6 companies. The data used in the form of financial statements with multiple regression analysis methods are processed using SPSS 23. The results of the study that the bonus mechanism affected the transfer pricing transaction with a significant value of 0.002, tunneling incentive affected the transfer pricing transaction, with a significant value of 0.004 and the debt covennat had no effect on the transfer pricing transaction with a significant value of 0.153.